Knowledge Discovery System - HASSAN, SITI FARAHAH (Universiti Teknologi Petronas, 2006)
Information and Knowledge are critical assets that organizations strive to obtain particularly from their competitors. However, they sometimes overlooked the important assets (information and knowledge) that lie inside the organization itself. The objective of the proposed project is to provide a means for organization to manage their intellectual capital via knowledge discovery system. In addition, this project focuses on developing a knowledge discovery system that aims to create a virtual workplace for people in organization where they can manage (upload, delete, download, edit, view and comment) their content and discover information and knowledge via automated categorized search features and peer reviews. These objectives aim to solve the problems that people within organizations usually have where they overlooked the experts resources they have, unable to find information resources when needed, and hard to communicate ideas or to share experience with people that have common interest. Waterfall model and Lotus Domino Designer 6 are used as the main methodology and tool to develop the proposed system. The developed project will provide a means ofcollecting, managing, sharing and locating information anddiscovery of knowledge within an organization.